External ocular motor palsies in ophthalmic zoster: a review. Issue 11 (November 1977) - Marsh, R J; Dulley, B; Kelly, V
Abstract : Seventy-seven new patients suffering from ophthalmic zoster and a selected group of 69 old patients were carefully examined with regard to external ocular movements. An incidence of 31% of ocular pareses was found in the new patients, and 58 in all were analysed. We were surprised to find several of these were contralateral and bilateral palsies. 28% of the palsies were asymptomatic, due to diplopia being present only in extremes of gaze and the rapid development of suppression in the affected eye. The theories of aetiology of these pareses are discussed.